Hybridization and its transformative role in bamboo fiber reinforced polymer composites: a review - Khan, Abir; Sapuan, S.M.; Zainudin, E.S.; Zuhri, M.Y.M. (Springer Science and Business Media B.V., 2024)
Design and development of environmentally friendly composite materials is underway in response to escalating environmental concerns and the looming scarcity of petroleum-based resources. A key strategy in this endeavor is the application of biologically derived polymers, reinforced with organic fbers. This approach has appeared to be a potent substitute for synthetic fber-reinforced polymers in the development of composite materials. Among the organic fbers, bamboo has seen a surge in popularity due to its wide availability, cost-efectiveness, biodegradability, and superior mechanical properties. However, bamboo fber is combined with other natural fbers in order to maximize the performance, address limitations, and broaden the scope of application of bamboo fber-reinforced hybrid polymer composites. This review covers topics including the anatomy of bamboo and the chemical composition of bamboo fber. Later on, diferent aspects of hybrid composites such as confgurations of fbers and polymers, orientation of fbers, mechanical properties, thermal properties, biodegradability and applications in aerospace, ballistic protection, automotive, structural, fltration, electrode, electromagnetic wave absorption, sensor technologies, and infrared shielding are discussed. This review also highlights several problems and solutions in the development of bamboo hybrid composites. This article ofers valuable perspectives and recommendations for those engaged in the feld of green composites, paving the way for the creation of sustainable materials suitable for diverse applications.